Platelet Transfusion Therapy (Anwer Khan Modern Medical College Journal, 2017)
Patients with severe thrombocytopenia are presumed to be at increased risk for bleeding, and consequently it has been standard practice for the past four decades to give allogeneic platelet transfusions to severely thrombocytopenic patients as supportive care. Platelet transfusions may be given either prophylactically to reduce the risk of bleeding, in the absence of clinical hemorrhage (prophylactic transfusions), or to control active bleeding when present (therapeutic transfusions). Platelets for transfusion can be prepared either by separation of units of platelet concentrates (PCs) from whole blood, which are pooled before administration, or by apheresis from single donors. Comparative studies have shown that the post transfusion increments, hemostatic benefit, and side effects are similar with either product. Thus, in routine circumstances, they can be used interchangeably. In most centers, pooled PCs are less costly. Single-donor platelets from selected donors are preferred when histocompatible platelet transfusions are needed. Both preparations can be stored for up to 5 days after collection at 20°C to 24°C with good maintenance of platelet viability. It is now uncommon for patients undergoing intensive chemotherapy or bone marrow transplantation to die of hemorrhage, but it is open to debate as to what degree platelet transfusions have been responsible for this change in outcome, given the many other advances in other aspects of supportive care.Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 40-46